The winners : a novel - Backman, Fredrik, 1981- (Simon & Schuster, 2022)
"Maya Andersson and Benji Ovich, two young people who left in search of a life far from the forest town, come home and joyfully reunite with their closest childhood friends. There is a new sense of optimism and purpose in the town, embodied in the impressive new ice rink that has been built down by the lake. Two years have passed since the events that no one wants to think about. Everyone has tried to move on, but there's something about this place that prevents it. The destruction caused by a ferocious late-summer storm reignites the old rivalry between Beartown and the neighboring town of Hed, a rivalry which has always been fought through their ice hockey teams. Maya's parents, Peter and Kira, are caught up in an investigation of the hockey club's murky finances, and Amat--once the star of the Beartown team--has lost his way after an injury and a failed attempt to get drafted into the NHL. Simmering tensions between the two towns turn into acts of intimidation and then violence. All the while, a fourteen-year-old boy grows increasingly alienated from this hockey-obsessed community and is determined to take revenge on the people he holds responsible for his beloved sister's death. He has a pistol and a plan that will leave Beartown with a loss that is almost more that it can stand"--